An investigation of attentional foci and their temporal patterns: A naturalistic study in expert figure skaters - Bernier, M.; Trottier, C.; Thienot, E.; Fournier, J. (The Sport Psychologist, 2016)
This study aimed to explore attentional foci and their temporal patterns in expert skaters in real competition situations. Individual self-confrontation interviews were held with 8 expert figure skaters while they watched their videotaped program performed in official competitions. Qualitative data analysis revealed that skaters used a substantial number of loci, which were classified by content and characteristics. Event listing was used to display the patterns of foci over time, revealing that skaters used distinct processes to prepare for, perform, and evaluate different program elements. These results highlighted the great flexibility and variability of attentional focus, according to circumstantial factors.